Potential of Residential Grid-Connected Photovoltaic System as the Future Energy Source in Malaysia - S S Abd Wahid; Z Nawawi; M. I. Jambak; M. A. B. Sidik; Y. Z. Arief; M. W. Mustafa; Z Adzis (IAES Indonesia Section, 2015)
Malaysia has started the implementation of solarenergy harvesting in 1998. Located at equatorial region, Malaysia hasa large potential for solar energy. This paper examines the currentenergy consumption and demand in Malaysia. The potential of solarenergy harvesting in Malaysia is described together with the suitablephotovoltaic construction. It also explains the plans conducted byMalaysia involving solar energy that covers investments and alsoprojects involved such as Malaysia Building Integrated Photovoltaic(MBIPV). Finally, this paper analyses the potential of having a gridconnectedPV system in a residential area. The positive and negativefindings in terms of cost and suitability of the system are explained